DEVELOPMENT OF MACAMI (MARI MEMBACA DAN MEMAHAMI) INSTRUMENT USING MACROMEDIA FLASH 8 IN PRIMARY SCHOOLS - Ermaida Dewi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2020)
The background of this research is an instrument of learning for reading comprehension which in general is still dominated by an instrument in the form of print out which makes the students’ interest to read is reduced. In addition, this instrument is usually done manually or handwritten so that the students’ work must be corrected manually and require some time to get the results. This study aims to develop instruments or measuring devices for reading comprehension in the Primary School in Pekanbaru and find out the feasibility of measuring devices for reading comprehension skills. This product is Macromedia Flash 8 based namely